2012
DOI: 10.1038/modpathol.2012.122
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA expression profiles associated with pancreatic adenocarcinoma and ampullary adenocarcinoma

Abstract: MicroRNAs have potential as diagnostic cancer biomarkers. The aim of this study was (1) to define microRNA expression patterns in formalin-fixed parafin-embedded tissue from pancreatic ductal adenocarcinoma, ampullary adenocarcinoma, normal pancreas and chronic pancreatitis without using micro-dissection and (2) to discover new diagnostic microRNAs and combinations of microRNAs in cancer tissue. The expression of 664 microRNAs in tissue from 170 pancreatic adenocarcinomas and 107 ampullary adenocarcinomas were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
106
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 135 publications
(112 citation statements)
references
References 43 publications
6
106
0
Order By: Relevance
“…Consistent with our results, previous studies found that miR-198 expression is higher in cancer, including retinoblastoma (Zhao et al, 2009), squamous cell carcinoma of the tongue (Wong et al, 2008), pancreatic adenocarcinoma and ampullary adenocarcinoma (Schultz et al, 2012), and hepatocellular carcinoma (Varnholt et al, 2008). This condition is explained by miR-198 that regulates the Livin expression in cancer cells.…”
Section: Discussionsupporting
confidence: 80%
“…Consistent with our results, previous studies found that miR-198 expression is higher in cancer, including retinoblastoma (Zhao et al, 2009), squamous cell carcinoma of the tongue (Wong et al, 2008), pancreatic adenocarcinoma and ampullary adenocarcinoma (Schultz et al, 2012), and hepatocellular carcinoma (Varnholt et al, 2008). This condition is explained by miR-198 that regulates the Livin expression in cancer cells.…”
Section: Discussionsupporting
confidence: 80%
“…The results for tissue miR-196a [12] and miR-196b [41] were pooled, as these miRNAs differ by only one nt (which is not within the seed region) and both have been shown to separate PDAC from chronic pancreatitis and normal pancreas samples with good accuracy [50]. These two tissue studies used univariate analyses, and when combined produced an unadjusted estimate of risk of mortality of HR 1.43 (95% CI: 0.80-2.56, P = 0.232; Additional file 7: Fig.…”
Section: Mir-196a/bmentioning
confidence: 99%
“…Twenty additional miRNAs were discovered to discriminate between PDAC, chronic pancreatic and normal pancreas [78]. Later, expression of miR-203 [78], miR-148a, miR-196b, miR-196a and miR-205 [79] were demonstrated to be altered in PDAC versus chronic pancreatitis. In addition, miRNA expression profiles have been recently used to distinguish PDAC from cholangiocarcinoma, two practically indistinguishable cancers using conventional histopathological and clinical characteristics [80].…”
Section: Review Vorvis Koutsioumpa and Iliopoulos Future Science Groupmentioning
confidence: 99%